2014
DOI: 10.4995/wrs.2014.1183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary linseed oil and Ganoderma lucidum or olive leaves supplementation on fatty acid composition and oxidative status of rabbits

Abstract: The aim of the present study was to evaluate the influence of natural antioxidant supplementation on the oxidative stress induced by a high proportion of polyunsaturated fatty acids (PUFA) in rabbit diets. Forty-eight SIKA rabbits (24 male, 24 female) were penned individually and after a 5-d adaptation period divided into 4 homogeneous groups (2.58±0.3 kg). The CONT-group received a diet with 60 g/kg palm fat, while the other 3 groups received a diet with 60 g/kg linseed oil which was either unsupplemented (CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…Interestingly, values seemed not to be linearly related to the supplementation period (13.4, 0.0, 5.6, 11.1 and 4.2% for B, S1, S2, S3 and S4 rabbits). Similarly to our findings, other researchers did not observe any differences in productive traits when linseed oil was added to the diet of growing rabbits (Maertens et al., ; Trebušak et al., ). Productive traits were also not affected by the dietary supplementation with 0.38 mg Se/kg diet (Dokoupilová et al., ).…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, values seemed not to be linearly related to the supplementation period (13.4, 0.0, 5.6, 11.1 and 4.2% for B, S1, S2, S3 and S4 rabbits). Similarly to our findings, other researchers did not observe any differences in productive traits when linseed oil was added to the diet of growing rabbits (Maertens et al., ; Trebušak et al., ). Productive traits were also not affected by the dietary supplementation with 0.38 mg Se/kg diet (Dokoupilová et al., ).…”
Section: Resultssupporting
confidence: 91%
“…Animals fed diet containing beef tallow exhibited higher saturated and lower polyunsaturated fatty acid contents in their meat than those fed soybean oil, demonstrating the quality of the lipid sources and the possibility of altering the fatty acid composition of meat by including these feedstuffs in animal diets to achieve healthier products. Thus, although some researches aimed at increasing meat enrichment in n-3 fatty acids has been focused on the addition of higher-cost lipid sources (Casado et al, 2013;Trebušak et al, 2014), in the present study it is observed that soybean oil, which is commonly used in rabbit diets, has a potential beneficial effect on increase the level of polyunsaturated fatty acids and contribute to the adequate balance of n-6:n-3 ratio of today´s consumer diet.…”
Section: Discussionmentioning
confidence: 67%
“…The risk of oxidative stress was demonstrated by Trebušak et al [25]: after 52 days of unprotected dietary linseed oil administration at a very high level (9% w/w), the malondialdehyde (MDA) was increased by 38% in plasma, 132% in liver, and 210% in muscles. In a second experiment, with 6% dietary linseed oil, after 22 days of feeding Trebušak et al [26] observed an MDA level in plasma that was half that in comparison with their previous trial and which was not changed with linseed oil diet, while, again, the MDA content was increased by 110% in liver and 257% in hindleg meat. In Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 18 January 2019 Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 18 January 2019 doi:10.20944/preprints201901.0188.v1…”
Section: Itemsmentioning
confidence: 85%